HeLP: Development of occupational protection mask against surgical smoke - Helenize Ferreira Lima Leachi; Renata Perfeito Ribeiro (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to describe a technological innovation in the development of an individual, ergonomic, sustainable and effective occupational respiratory protection mask for workers exposed to surgical smoke. Methods: applied, exploratory, quantitative research, using design methods and tools: Sense Intent, Know Context, Know People, Frame Insights, Explore Concepts, Frame Solutions, Realize Offerings, in addition to the Product Development Process tools. It was developed from March 2019 to December 2021. Results: from the prototyping mold, it became possible to represent the abstract to the physical, where all the concepts created in the methodological steps were implemented and the necessary adjustments were made to create the model as a technological innovation, which will have the concept for product commercialization. Conclusions: a mask for protection against surgical smoke (HeLP) was developed, from the design step to the prototype development, being a technological innovation.